Phytobacteriology : - Janse, J. D. (CABI Publishing, 2005)
This book is a comprehensive manual of phytobacteriology and is rich in illustration. Its starts by briefly outlining the history and science of bacteriology and gives an overview of the diversity and versatility of bacteria. It goes on to explain diagnosis of bacterial plant diseases including detection, characterization and identification of plant-pathogenic bacteria using conventional and molecular methods and furthermore how bacteria can cause disease and how plant react to this. It also discusses the epidemiology and economic importance of bacterial diseases and strategies for their prevention and control in order to reduce crop losses.